Parallel Simplex Method Improvements - Bashir Salih; Muhammad Ali (Al-Rafidain Journal of Computer Sciences and Mathematics)
The aim of the project is to develop parallel approaches for both the simplex that are used in linear programming to solve linear module systems. Most of these models are time consuming when executed and processed in the sequential microprocessor computers. During the project, we try to decrease this time and increase the efficiency of the algorithm for the two methods simplex, through developing parallel methods appropriate to be executed on MIMD type computers. In this paper, three algorithms were suggested for paralleling (a developed algorithm and a comparison was made between the three algorithms and the original. This comparison is included in second section. In general, the practical results and the suggested programs for these new algorithms proved to be better in performance than their analogues that are executed in computers of sequential processor in view of the two elements of execution time and algorithm time.